Breakdown of utilitarian moral judgement after basolateral amygdala damage - van Honk, Jack; Terburg, David; Montoya, Estrella R.; Grafman, Jordan; Stein, Dan J.; Morgan, Barak (Proceedings of the National Academy of Sciences - PNAS, 2022)
Most of us would regard killing another person as morally wrong, but when the death of one saves multiple others, it can be morally permitted. According to a prominent computational dual-systems framework, in these life-and-death dilemmas, deontological (nonsacrificial) moral judgments stem from a model-free algorithm that emphasizes the intrinsic value of the sacrificial action, while utilitarian (sacrificial) moral judgments are derived from a model-based algorithm that emphasizes the outcome of the sacrificial action. Rodent decision-making research suggests that the model-based algorithm depends on the basolateral amygdala (BLA), but these findings have not yet been translated to human moral decision-making. Here, in five humans with selective, bilateral BLA damage, we show a breakdown of utilitarian sacrificial moral judgments, pointing at deficient model-based moral decision-making. Across an established set of moral dilemmas, healthy controls frequently sacrifice one person to save numerous others, but BLA-damaged humans withhold such sacrificial judgments even at the cost of thousands of lives. Our translational research confirms a neurocomputational hypothesis drawn from rodent decision-making research by indicating that the model-based algorithm which underlies outcome-based, utilitarian moral judgements in humans critically depends on the BLA.